Risk Factors That Cause Stunting in Indonesia - Arief Andriyanto; Faisal Ibnu; Rina Nur Hidayati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
The Sustainable Development Goals emphasizing an intervention to prioritize solutions to the global challenge of poor child development in low and middle income countries (LMICs). In 2015, about 25% of children under five years of age in low were stunted (Kim & Subramanian, 2017; Perkins et al., 2017; UNICEF, 2015) The WHO conceptual framework for stunting (2013) identified household and family factors, complementary feeding, breastfeeding practices and infections as the most plausible causes of stunting(Stewart, Iannotti, Dewey, Michaelsen, & Onyango, 2013)